Pembelajaran Praktek Manasik Haji Terhadap Peningkatan Pemahaman dan Keterampilan Fikih Haji dan Umroh - Mahathir Akbar (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2023)
Hajj ritual training is basically a means of introducing the values and practices of the pilgrimage. Materials of pilgrimage as general worship materials cannot be mastered properly without a balance between theory and practice. Because of this, the Hajj rituals, which are part of the program from the Worship Practice Laboratory (LPI) of IAIN Syekh Nurjati Cirebon, by collaborating with several KBIHUs in Cirebon City/Regency, uses a learning approach to the theories and practices of Hajj rituals to improve the quality of understanding of a total of 6,000 students from the fourth semester ( IV) and six (VI) IAIN Syekh Nurjati Cirebon for the 2021-2022 class. LPI's successful implementation of the Hajj ritual training activities is evidenced by the high enthusiasm and interest of the students who took part in this activity. Not only students, but lecturers were also involved as mentors. Some of the benefits of this Manasik Training Activity include: increasing students' understanding and skills of the pilgrimage; motivating to perfect the pillars of Islam (Hajj worship); increasing understanding and skills as well as motivating the community, in this case teaching staff (lecturers) and other stakeholders involved in implementation. So training in Hajj rituals is important in increasing the understanding and skills of the pilgrimage not only for students but also for lecturers and others.